The Essential DNA Damage Response Complex MRN Is Dispensable for the Survival and Function of Purkinje Neurons - Ding, Mingmei; Qing, Xiaobing; Zhang, Guangyu; Baade-Büttner, Carolin; Gruber, Ralph; Lu, Haizhen; Ferguson, David O.; Geis, Christian; Wang, Zhao-Qi; Zhou, Zhong-Wei (Frontiers in Aging Neuroscience, 2022)
MRE11, RAD50, and NBS1 form the MRN complex in response to DNA damage to activate ATM, a gene responsible for Ataxia-Telangiectasia (A-T). Loss of any components of the MRN complex compromises cell life. Mutations in MRE11, RAD50, and NBS1 cause human genomic instability syndromes Ataxia-Telangiectasia-like disorder (A-TLD), NBS-like disorder (NBSLD), and Nijmegen Breakage Syndrome (NBS), respectively. Among other pathologies, neuronal deficits, including microcephaly, intellectual disabilities, and progressive cerebellar degeneration, are common in these disorders. Nbs1 deletion in neural stem cells of mouse models resulted in cerebellar atrophy and ataxia, mimicking the A-T syndrome suggesting an etiological function of MRN-mediated DDR in neuronal homeostasis and neuropathology. Here we show that deletion of Nbs1 or Mre11 specifically in Purkinje neurons of mouse models (Nbs1-PC∆ and Mre11-PC∆, respectively) is compatible with cerebellar development. Deleting Nbs1 in Purkinje cells disrupts the cellular localization pattern of MRE11 or RAD50 without inducing apparent DNA damage, albeit impaired DNA damage response (judged by 53BP1 focus formation) to ionizing radiation (IR). However, neither survival nor morphology of Purkinje cells and thus locomotor capabilities is affected by Nbs1 deletion under physiological conditions. Similarly, deletion of Mre11 in Purkinje cells does not affect the numbers or morphology of Purkinje cells and causes no accumulation of DNA damage. Mre11-deleted Purkinje cells have regular intrinsic neuronal activity. Taken together, these data indicate that the MRN complex is not essential for the survival and functionality of postmitotic neurons such as Purkinje cells. Thus, cerebellar deficits in MRN defect-related disorders and mouse models are unlikely to be a direct consequence of loss of these factors compromising DDR in postmitotic neurons such as Purkinje cells.